Pendeteksian Kecurangan Laporan Keuangan dengan Beneish M-Score pada Perusahaan Perbankan Terbuka - Yanuary Eka Christy; Daniel Sugama Stephanus (Jurnal Akuntansi Bisnis, 2018)
This study aims to determine the percentage of firms listed on the BEI in 2014-2016 which are classified as non manipulator, gray company and manipulator by using five indexes of Days Sales in Receivable Index (DSRI), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), and Total Accrual To Total Assets Index (TATA). The method of collecting data is documentation with the number of samples are 42 banking companies listed on BEI Year 2014-2016. Data analysis used is Beneish Ratio Index. The results revealed that the percentage of banking companies classified as non manipulator in 2014 amounted to 4.76%, by 2015 38.1% and in 2016 47.6%. The percentage of banking companies classified as gray company in 2014 amounted to 38.1%, by 2015 50% and in 2016 45.2%. Percentage of banking companies that are classified as manipulators in 2014 amounted to 57.1%, in 2015 11.9% and in 2016 7.14%.